Comparing real-world outcomes of total neoadjuvant treatment and CRT at a tertiary medical center - Turfa, Rim; Alawabdeh, Tala; Naser, Ayman; Alamro, Yazan; Albliwi, Moath; Almasri, Sama; Al Qazakzeh, Abdullah; Shattal, Mohammad Abu; Dabous, Ali; Amarin, Rula (Frontiers in Oncology, 2023)
Introduction For years, standard treatment for locally advanced rectal cancer (LARC) has included neoadjuvant chemoradiotherapy (CRT), followed by surgery and adjuvant chemotherapy. Although CRT has helped reduce local recurrence rates, it hasn’t consistently improved overall survival. Recent trials have unveiled a different approach called total neoadjuvant treatment (TNT), involving pre-surgery radiotherapy followed by chemotherapy (CAPOX/FOLFOX). TNT shows promise with improved treatment response and lower distant metastasis rates without compromising local control. Consequently, many healthcare institutions have adopted TNT as their preferred neoadjuvant treatment. This study, conducted at a tertiary center, compares the real-world outcomes of both CRT and TNT protocols. Methods In this retrospective study of 390 patients treated between 2015 and 2021, aged 18 or older with LARC and tumors within 12 cm of the anal verge, we compared treatment outcomes. We assessed factors like pathological complete remission (pCR), three-year event-free survival (EFS), and overall survival (OS) between the two treatment groups using the Chi-squared test. Results Out of the 390 eligible patients, 256 underwent CRT, while 84 received TNT. Surgery was performed on 215 (84%) patients in the CRT group, compared to 55 (65.5%) in the TNT group. Notably, 33 (12.8%) achieved pCR in the CRT group, whereas 23 (27.7%) achieved pCR in the TNT group (P <.001). Regardless of whether surgery was performed or not, the TNT group exhibited lower recurrence rates (12.7% vs. 18.6% with surgery, 28.6% vs. 45% without surgery). The 3-year EFS rate was 80% in the CRT group and 90% in the TNT group (P = .05). Additionally, the 3-year OS rates favored the TNT group, standing at 96.4% compared to 84.4% in the CRT group (P = .005). Conclusion Our findings indicate that patients who underwent TNT demonstrated a higher likelihood of achieving pCR and experienced lower recurrence rates compared to those in the CRT group. Additionally, the TNT group exhibited superior 3-year EFS and OS. It is important to note, however, that a longer follow-up period is required to further validate these results.